2014
DOI: 10.1590/s2236-89062014000200007
|View full text |Cite
|
Sign up to set email alerts
|

Comunidade de fungos Agaricomycetes em diferentes sistemas florestais no noroeste do Estado do Rio Grande do Sul, Brasil: Floresta Estacional Decídua e monocultura de eucalipto

Abstract: -(Agaricomycetes fungi community at different forest systems in the northwest of Rio Grande do Sul State, Brazil: seasonal deciduous forest and eucalypt monoculture). Monocultures differ from native forests in relation to plant heterogeneity, variety of substrates, and soil humidity, possibly altering the diversity of organisms, such as the fungi. This study aimed to compare the richness, abundance, and composition of Agaricomycetes fungi in a native forest and in a eucalypt monoculture. The fungi were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
0
5
0
2
Order By: Relevance
“…In general, fungi depend on environmental variables, including rainfall, soil moisture, temperature and variety of existing substrates (LAZAROTTO et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…In general, fungi depend on environmental variables, including rainfall, soil moisture, temperature and variety of existing substrates (LAZAROTTO et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…During this period it was observed that in some treatments there was variation, with the indexes of richness and diversity, equity and dominance of fungi in the period due to rainfall. The importance of precipitation in studies such as this one is that it is a variable that has a direct influence on the abundance and richness of fungi in native vegetation (LAZAROTTO, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…(2008a). Color descriptions were based on Küppers (2002). All specimens were deposited at the herbarium of the Universidade Federal do Rio Grande do Norte (UFRN, Brazil).…”
Section: Methodsmentioning
confidence: 99%
“…In Brazil, Geastrum fimbriatum has been reported from: Bahia (Trierveiler-Pereira & al., 2009), Paraíba (Trierveiler-Pereira & al., 2011, Pará (Leite & al., 2011;Trierveiler-Pereira & al., 2011), Pernambuco (Leite & al., 2007a;Trierveiler-Pereira & al., 2011), Rio de Janeiro (Berkeley & Cooke, 1876;Hennings, 1904b;Saccardo, 1888), Rio Grande do Norte (Sousa & al., 2014c), and Rio Grande do Sul (Rick, 1961;Lazarotto & al., 2014).…”
Section: Earthstars From Minas Geraismentioning
confidence: 99%